2021
DOI: 10.3390/ijms22041575
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Polypeptide that Mimics the Integrin Binding Site for EDA Fibronectin to Block Profibrotic Cell Activity

Abstract: Fibrosis is characterized by excessive production of disorganized collagen- and fibronectin-rich extracellular matrices (ECMs) and is driven by the persistence of myofibroblasts within tissues. A key protein contributing to myofibroblast differentiation is extra domain A fibronectin (EDA-FN). We sought to target and interfere with interactions between EDA-FN and its integrin receptors to effectively inhibit profibrotic activity and myofibroblast formation. Molecular docking was used to assist in the design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The accumulation of EDA-FN has been observed in multiple fibrotic disorders, including lung, liver, and skin [100,[105][106][107]. EDA-FN promotes myofibroblast differentiation by orchestrating LAP/LTBP release and activation of TGF-β1 [108], increasing matrix stress-strain tension [109,110], and by activating mechanotransducer-integrin signalling via FAK activation [111][112][113][114]. Research by Shinde et al [115] and Kohan et al [112] demonstrated that fibroblast-expressed integrins, α4β1 (VLA-4) and α4β7 (LPAM-1), mediate different roles in myofibroblast formation, respectively.…”
Section: Mechanotransductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of EDA-FN has been observed in multiple fibrotic disorders, including lung, liver, and skin [100,[105][106][107]. EDA-FN promotes myofibroblast differentiation by orchestrating LAP/LTBP release and activation of TGF-β1 [108], increasing matrix stress-strain tension [109,110], and by activating mechanotransducer-integrin signalling via FAK activation [111][112][113][114]. Research by Shinde et al [115] and Kohan et al [112] demonstrated that fibroblast-expressed integrins, α4β1 (VLA-4) and α4β7 (LPAM-1), mediate different roles in myofibroblast formation, respectively.…”
Section: Mechanotransductionmentioning
confidence: 99%
“…developed a small blocking polypeptide to bind and block EDA-FN interactions with the α4β1 binding cleft, with high specificity [114]. The polypeptide, AF38Pep, was designed to mimic the integrin α4β1 receptor site for the EDGIHEL motif of EDA-FN and was shown to interfere with TGF-β1-stimulated fibroblast-myofibroblast formation by the specific blockade of integrin α4β1 signalling, the inhibition of FAK activation, and the prevention of profibrotic gene transcription [114]. The aforementioned first generation of small blocking polypeptides have revealed the renewed promise of the specific interruption of integrin-mediated mechanotransduction and myofibroblast formation.…”
Section: Experimental and Pre-clinical Interventions For Myofibroblast Differentiationmentioning
confidence: 99%
“…Finally, these proteins are linked to the actin cytoskeleton through an "actin binding layer", which consists of α-actinin, vasodilator-simulated phosphoprotein (VASP), and zyxin [62]. Beneath the listed proteins, many other cellular key players, such as sarcoma (Src)-family kinases or the extracellular signal-regulated kinases 1/2 (ERK1/2) have been shown to directly interact with FAs and regulate the activity and assembly status of its components (Figure 1A) [15,63,64].…”
Section: The Ecm Focal Adhesions and Adherens Junctions In Periodontal Health And Diseasementioning
confidence: 99%
“…It is found in a soluble form in liver and blood [ 9 ] and secreted by different cells such as endothelial cells and fibroblasts in insoluble form [ 10 ]. Several studies have underlined the considerable implication of FN in a variety of biological processes especially in cytoskeletal assembly, cell attachment, and migration [ 11 , 12 ], since its different domains are specific ligands for a variety of ECM proteins principally collagen [ 13 , 14 ] and heparin [ 15 ] as well as integrins cell surface receptors [ 16 , 17 , 18 ]. Therefore, controlling FN-integrins-specific interactions offers an innovative strategy to engineering biofunctionalized surfaces promoting cellular adhesion and stimulating cellular proliferation and migration [ 11 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other observations indicate the loss of conformation while proceeding to adsorption of native FN on several supports leading to a reduced cell receptor response [ 27 ]. To circumvent these drawbacks, researchers tended to engineer small recombinant protein fragments deriving from functional ECM protein domains ensuring oriented bioactivity with reduced cost and improved affinity [ 18 , 28 ] as well as enabling the design of novel combined recombinants fragments for additional activities [ 22 , 29 , 30 , 31 ]. In this case, the fusion tag technology has been extensively used for recombinant fragments production to allow efficient purification with reduced time and cost when compared to native ECM protein purification [ 32 ].…”
Section: Introductionmentioning
confidence: 99%